Pengaruh Pengalaman Bersantap di Koral Restaurant Terhadap Loyalitas Pengunjung Restoran sebagai Destination Dining di Bali - Marylin, Stefanny (Politeknik Pariwisata Medan, 2025)
Current tourism trends indicate a shift from merely consuming accommodation services to seeking holistic experiences, particularly in the culinary domain. One prominent phenomenon is destination dining—restaurants that serve as primary attractions rather than just hotel amenities. Koral Restaurant, located within the premises of The Apurva Kempinski Bali, exemplifies destination dining in Indonesia. As Bali’s first underwater restaurant, Koral attracts visitors from various regions and countries, including many who do not stay at the hotel. This study aims to explore the influence of the dining experience at Koral Restaurant on visitor loyalty, particularly among those who consider Koral a primary culinary destination. A descriptive qualitative approach was employed using content analysis of online reviews published across platforms such as TripAdvisor, Google Reviews, travel blogs, and online forums. The data was collected from reviews posted between 2023 and 2024 that met the criteria of relevance, narrative depth, and expressed visitor perceptions. The findings reveal that four key elements—underwater visual atmosphere, food quality and presentation, personalized service, and revisit intention—contribute significantly to shaping visitor loyalty. This study affirms that Koral Restaurant has established itself as a standalone culinary destination, transcending its role as a typical hotel restaurant.